Tahlîlu al-Akhta’ an-Nahwiyyah ‘an al-Asma’ al-Marfu’ật fi Qirậ’ah an-Nushûs al-Arabiyah lada Talậmizi as-Shaffi at-Tsaniy Asyara bi Madrasati Miftậhil Hidậyah at-Tsanawiyah al-Islậmiyah Bakanbaru - Lubis, Riska Wani; Hendri, Muspika (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
تحليل الأخطاء النحوية عن الأسماء المرفوعات في قراءة النصوص العربية لدى تلاميذ الصف الثاني عشر بمدراسة مفتاح الهداية الثانوية الإسلامية بكنبارو Riska Wani Lubis, Muspika hendriUniversitas islam negeri sultan syarif kasim riauriskwanilubis@gmail.commuspika.hendri@uin-suska.ac.id ABSTRACTIn learning a foreign language, of course, there are difficulties which are the cause of errors. It is motivated by the mistakes of nahwu or I'rab students, especially in the isim-isim that are made in reading Arabic texts that have been studied previously. This researcher is a qualitative research with a descriptive method with the aim of analyzing and interpreting Nahwu's errors about isim-isim that are fabricated in reading the asrab text of grade XII students of Madrasah Aliyah Miftahul Hidayah Pekanbaru. The subjects in this study are the students and objects used in the nahwu research on isim-isim that are created in reading Arabic texts for grade XII students of Madrasah Aliyah Miftahul Hidayah Pekanbaru. The data collection techniques used are tests and documentation. This study shows that the most common mistakes among students in Arabic texts are when reading sentences that are in the position of fail and Naibul fail where students who made mistakes in reading files amounted to 11 people out of a total of 30 subjects and in naibul files amounted to 19 people from 30 subjects. Keywords: Error Analysis, Isim Isim Revealed, Maharah Qiroah